Compact Coplanar Waveguide Antenna Using Arm Patch for Software Defined Radio - Nurul Fahmi Arief Hakim; Silmi Ath Thahirah Al Azhima; Mariya Al Qibtiya (Jurnal Elektronika dan Telekomunikasi, 2023)
This article proposes a compact coplanar waveguide (CPW) antenna with a semicircular patch and patch arm above the feed line. The method used in this antenna research is experimental, with antenna parameter optimization, fabrication, and measurement steps. The antenna was 40 mm × 46 mm × 0.8 mm and was printed on an FR4 substrate. Antenna optimization was carried out with CST Studio Suite to obtain optimal results. Based on return loss measurement results, the proposed antenna has an operational frequency of 2 GHz–7 GHz. The antenna arm has a significant effect on the operational frequency of the antenna, as proven by a parameter study of the antenna arm. Parametric studies were carried out on the antenna by investigating the influence of geometric parameters on the frequency characteristics. Optimization results were printed then measured by a Vector Network Analyzer (VNA) and a spectrum analyzer. The fabricated CPW antenna has a wider operating frequency than the simulation. An omnidirectional radiation pattern was observed at 2 GHz–4 GHz. The antenna has been used as a transmitter and receiver at 2.4 GHz, 3 GHz, and 4 GHz. The antenna is able to receive the signal emitted from the signal generator.